2020
DOI: 10.1212/nxi.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Contactin-1 autoimmunity

Abstract: ObjectiveTo determine serologic characteristics, frequency, phenotype, paraneoplastic associations, and electrodiagnostic and histopathologic features accompanying contactin-1 autoimmunity.MethodsArchived sera known to produce synaptic tissue-based immunofluorescence patterns were reevaluated, and contactin-1 specificity was confirmed by recombinant protein assays. Screening of 233 chronic/relapsing demyelinating neuropathies for additional cases was performed.ResultsWe identified 10 contactin-1 IgG seropositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
(19 reference statements)
2
27
0
Order By: Relevance
“…Two patients (1 with CISP and 1 with CISP-plus) were positive for contactin-1 antibodies, which are known to be associated with inflammatory sensory-predominant neuropathies. 5 , 6 Finding co-occurring autoimmune diseases supports our hypothesis that CISP-plus and CISP are immune-mediated neuropathies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Two patients (1 with CISP and 1 with CISP-plus) were positive for contactin-1 antibodies, which are known to be associated with inflammatory sensory-predominant neuropathies. 5 , 6 Finding co-occurring autoimmune diseases supports our hypothesis that CISP-plus and CISP are immune-mediated neuropathies.…”
Section: Discussionsupporting
confidence: 73%
“…Although chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) usually presents with weakness, 1 , 2 sensory-predominant forms have been described, 3 , 4 including the recently recognized paranodal neuropathies (contactin-1–associated CIDP). 5 , 6 In 2004, our group described a restricted form of sensory CIDP, chronic immune sensory polyradiculopathy (CISP), characterized by selective involvement of sensory nerve roots. 7 A similar acute form of immune-mediated pure sensory polyradiculopathy has been described recently.…”
mentioning
confidence: 99%
“…IgG4 is regarded as the main pathogenic IgG subtype of anti-CNTN1 antibodies. Similar to previous studies, our patients showed few responses to IVIg when they visited our clinic (9,17). This may be because the major effector function of IVIg is complement binding through binding to various Fc receptors and complement activation, while IgG4 does not bind Fc receptors and does not activate the complement pathway (18).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to other IgG4 autoimmune diseases such as myasthenia gravis with antibodies to muscle-specific kinase (MuSK-MG), anti-CNTN1 autoimmune nodopathy generally responds well to rituximab, a monoclonal antibody against B lymphocyte membrane protein CD20 (5,6). Specifically, improvements in neurological symptoms including gait, tremor, muscle strength, and a decrease in antibody titer can be seen, especially in those who are resistant to IVIg and prednisone (7)(8)(9). However, the high cost of the common-dose rituximab regimen such as 375 mg/ m 2 /week over 4 weeks, and some adverse events have restricted its widespread use in China.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies focusing on the clinical symptoms of anti-CNTN1 seropositive patients reported sensory ataxia as one of the disabling symptoms, 12 , 20 , 26 , 27 raising the suspicion that the paranodes may not be the only site of pathogenicity. DRG are easily accessible by autoantibodies because of the lack of a sufficient neurovascular barrier, 28 and our data give evidence of a direct effect of anti-CNTN1 autoantibodies on DRG, thus supporting the notion of DRG as another site of pathogenicity.…”
Section: Discussionmentioning
confidence: 99%